Nexus between Nuclear Energy, Economic Growth, and Greenhouse Gas Emissions in India - Raihan, Asif; Zimon, Grzegorz; Alam, Mohammad Mahtab; Khan, Md. Rehan; Sadowska, Beata (International Journal of Energy Economics and Policy, 2024)
The escalating demand for fossil fuels in India has resulted in a significant strain on the environment due to the amplified emissions of greenhouse gases (GHGs). Nevertheless, India possesses a significant capacity for nuclear energy, as seen by its 22 operational nuclear reactors. This capacity holds promise for reducing GHG emissions. This research utilized a dataset spanning from 1969 to 2021 to examine the impact of nuclear energy utilization on GHG emissions. The study also aimed to verify the validity of the environmental Kuznets curve (EKC) hypothesis in India, employing the Autoregressive Distributive Lag (ARDL) model. The findings suggest that the EKC is applicable to India. Furthermore, it has been observed that a marginal increase of 1% in the use of nuclear energy leads to a reduction of GHG by 0.02% in the immediate term and 0.16% in the long term. This finding highlights the significance of expanding nuclear power as a crucial policy objective in order to attain environmentally friendly and sustainable economic development.